2014
DOI: 10.1557/mrc.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

Lithium oxide solution in chloride melts as a medium to prepare LiCoO2 nanoparticles

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In recent years, more advanced molten salt methods for the synthesis of niobates of alkali, alkaline earth, rare earth, and transition metals in the shape of nanopowders with different particle morphology have been proposed and tested [ 29 , 30 , 31 , 32 ]. These methods enable to decrease the process temperature by hundreds of degrees in contrast to solid-phase synthesis, to ensure uniform distribution of the precursor particles in the reaction medium, to increase the rate of the synthesis, to control the morphology and size of reaction products, and to reduce their tendency to agglomeration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, more advanced molten salt methods for the synthesis of niobates of alkali, alkaline earth, rare earth, and transition metals in the shape of nanopowders with different particle morphology have been proposed and tested [ 29 , 30 , 31 , 32 ]. These methods enable to decrease the process temperature by hundreds of degrees in contrast to solid-phase synthesis, to ensure uniform distribution of the precursor particles in the reaction medium, to increase the rate of the synthesis, to control the morphology and size of reaction products, and to reduce their tendency to agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…Judging by the publications, these and other thermally stable salts were not considered as the precursors to synthesize complex oxides. A number of our works [ 31 , 32 ] showed that the use of halide melts as precursors create more suitable conditions for the synthesis of nanosized particles. The logical development of these studies is the use of heat-resistant chloride melts to change the chemical composition of complex oxide powders and obtain thin films on single-crystal surface.…”
Section: Introductionmentioning
confidence: 99%